How and when cyberloafing affect innovative work behavior? - Hendryadi Hendryadi (Jurnal Riset Manajemen dan Bisnis, 2024)
Cyberloafing has traditionally been viewed as counterproductive work behavior that detracts from employee productivity. However, emerging research suggests it may offer unexpected benefits. This study investigates how and when cyberloafing affects innovative work behavior by examining the mediating role of knowledge acquisition and the moderating role of time of day. A two-wave survey was conducted with 342 employees in technology companies. At Wave 1, employees reported their cyberloafing frequency and job demands; at Wave 2, they reported knowledge acquisition, while supervisors rated their innovative work behavior. A multi-group analysis using covariance-based SEM compared employees before 12 PM and after 12 PM. The findings reveal that knowledge acquisition mediates the relationship between cyberloafing and innovative work behavior, but this mediation is contingent on time of day. Before 12 PM, cyberloafing influences innovation indirectly through knowledge acquisition, suggesting a learning-oriented mechanism. After 12 PM, cyberloafing directly affects innovation, potentially through restorative mechanisms that replenish cognitive resources. This study advances understanding of cyberloafing as a multifaceted phenomenon with both learning and restorative functions, demonstrating that its effects on innovation are not uniform but depend critically on when it occurs. Organizations should consider differentiated policies that recognize the temporal dynamics of cyberloafing.